ХAЛҚAРО AЛОҚAЛAРДA КОНТИНЕНТAЛ МУНОСAБAТЛAРНИНГ УСТУВОРЛИГИ - М.Л. Фaйзиходжaевa (Journal of new century innovations, 2023)
Anntatin: this article is devted t the imprtance f integratin int internatinal transprt crridrs, and thrugh internatinal glbalizatin, the emergence f new qualitative and qualitative parameters and technlgical prcesses in the netwrk has been studied.